👤

aratati ca ctg pi/8-tg pi/8=2​

Răspuns :

Răspuns:

Explicație pas cu pas:

Avem formula

[tex]\tan\dfrac{x}{2}=\sqrt{\dfrac{1-\cos x}{1+\cos x}}, \ x\in\left[0,\pi\right)[/tex]

Atunci

[tex]\tan\dfrac{\pi}{8}=\tan\dfrac{\frac{\pi}{4}}{2}=\sqrt{\dfrac{1-\cos\frac{\pi}{4}}{1+\cos\frac{\pi}{4}}}=\sqrt{\dfrac{1-\frac{\sqrt{2}}{2}}{1+\frac{\sqrt{2}}{2}}}=\sqrt{\dfrac{2-\sqrt{2}}{2+\sqrt{2}}}=\\=\dfrac{2-\sqrt{2}}{\sqrt{2}}=\sqrt{2}-1[/tex]

Atunci

[tex]\cot\dfrac{\pi}{8}=\dfrac{1}{\sqrt{2}-1}[/tex]

Rezultă

[tex]\cot\dfrac{\pi}{8}-\tan\dfrac{\pi}{8}=\dfrac{1}{\sqrt{2}-1}-(\sqrt{2}-1)=\dfrac{1-(\sqrt{2}-1)^2}{\sqrt{2}-1}=\dfrac{2(\sqrt{2}-1)}{\sqrt{2}-1}=2[/tex]

Răspuns:

Explicație pas cu pas:

ctg a/2=sin a/(1-cos a)  si tg a/2=sin a/(a+cos a)

ctg π/8=sin π/4/(1-cosπ/4)=√2/2/(1-√2/2)=√2/(2-√2)=1/(√2-1)

tg π/8=sin π/4/(1+cosπ/4)=√2/(2+√2)=1/(√2+1)

ctg π/8-tgπ/8=1/(√2-1)-1/(√2+1)=(√2+1)/(2-1)-(√2-1)/(2-1)=

   =√2+1-√2+1=2